Mediation of endothelial activation and stress index in the association between vitamin B6 turnover rate and diabetic retinopathy: an analysis of the National Health and Nutrition Examination Survey - Yin, Jie; Chen, Juan; Chen, Yuanyuan (Frontiers in Nutrition, 2025)
AimThis study aimed to explore the association between the ratio of 4-pyridoxine (4-PA) to pyridoxal 5′-phosphate (PLP) (4-PA/PLP) and diabetic retinopathy (DR) and further assess the mediating effect of Endothelial Activation and Stress Index (EASIX) on the association between 4-PA/PLP and DR.MethodsIn this cross-sectional study, 1,698 patients with diabetes from the National Health and Nutrition Examination Survey were included. According to the median, 4-PA/PLP was categorized into a high-level group (≥0.89) and a low-level group (<0.89). As the EASIX had a skewed distribution, it was log-transformed before analysis. Weighted logistic regression models were used to investigate the association of 4-PA/PLP with EASIX and DR and the mediating effect of EASIX on the association between 4-PA/PLP and DR. The distribution-of-product method was adopted to assess the mediating effect. Subgroup analysis was performed based on the age and duration of diabetes.ResultsA total of 362 diabetic patients were classified as having DR. After adjusting for all covariates, a higher level of 4-PA/PLP was associated with an increased level of log EASIX [odds ratio (OR) = 1.56, 95% confidence interval (CI): 1.06–2.30]. A higher ratio of 4-PA/PLP was associated with increased odds of DR compared to the reference group with lower levels of 4-PA/PLP (OR = 1.94, 95%CI: 1.40–2.67). In addition, we found that log EASIX may play a mediating role in the 4-PA/PLP and DR, with a 95% CI of distribution of product of 0.31 (95% CI: 0.02–0.67). The proportion of mediation was 69.06%. The mediating effect of log EASIX was also observed in individuals with diabetes who were aged≥60 years (proportion of mediation: 50.63%) or had a duration of diabetes ≥10 years (proportion of mediation: 71.83%).ConclusionThis study found a positive association between high levels of 4-PA/PLP and an increased risk of DR, with the relationship being partially mediated by log EASIX.